CLIMATE IN SOFTWARE DEVELOPMENT TEAMS: ROLE OF TASK INTERDEPENDENCE AND PROCEDURAL JUSTICE - M. P. Ganesh, (Asian Academy of Management Journal, 2013)
The objective of the study is to understand the role of task interdependence and procedural justice in influencing climate in software development teams. Data was collected from 192 software professionals from 33 software development teams. Team climate was measured using Team Climate Inventory by Anderson and West. Procedural justice was measured using a scale developed by Colquitt. Pearce and Gregersen's scale was used to measure task interdependence within the team. Teams were taken as the unit of analysis. Regression was used to study the moderating and main effects.Results showed a postive impact of task interdependence on all the sub dimensions of team climate. Procedural justice had a positive effect on two sub-dimensions of team climate (participatory safety and support for innovation). Perception of procedural justice also helped to improve the positive effect of task interdependence on the members' perception of support for innovation within their team.